GAMBARAN PELAKSANAAN DAN PENCATATAN ADMINISTRASI PELAYANAN KEGIATAN UKBM DI WILAYAH KERJA PUSKESMAS TIRON - Reny Nugraheni (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2025)
Health services at the community health center (Puskesmas) level, particularly through the activities of Non-Hospital Health Units (UKBM), play a crucial role in enhancing access to and the quality of healthcare services for the community. However, the implementation and documentation of administrative activities for UKBM in several regions often face challenges, such as inaccurate data, lack of coordination among staff, and suboptimal recording systems. This study aims to describe the implementation and documentation of administrative activities for UKBM services in the Puskesmas Tiron Work Area and identify the factors affecting its effectiveness. This study uses a descriptive approach with survey and interview methods. Data were collected through direct observation, interviews with Puskesmas staff, and analysis of administrative documents related to UKBM activities in the region. Participants in this study included the head of the Puskesmas, medical personnel, and administrative staff involved in UKBM activities. The results of the study indicate that the implementation of UKBM activities at Puskesmas Tiron has been generally good, but there are still some shortcomings in coordination and administrative documentation. The documentation process still uses manual methods that are prone to errors and data loss. Additionally, there are obstacles in monitoring and evaluating activities, which hinder the efficiency of managing UKBM services. Data analysis shows that the main challenge in implementing UKBM activities is the lack of trained human resources in administrative management, as well as limited facilities and infrastructure to support documentation and reporting. Furthermore, the administrative system that has not been well-integrated causes delays in data entry and reporting, which affects the quality of services. This study suggests that Puskesmas Tiron optimize the use of information technology to improve the efficiency of administrative documentation and minimize errors in data entry. Training and skill development in administration for Puskesmas staff are also essential to improve the management quality of UKBM activities. Moreover, stronger collaboration between relevant parties, both at the Puskesmas level and with other health agencies, should be reinforced to support more coordinated and effective implementation of activitas.